Risk Stratification Techniques for Sudden Death - Talajic, Mario; Costantini, Otto; La Rovere, Maria Teresa; Glass, Leon (MD Conference Express, 2006)
Challenges in the identification of individuals at high risk for sudden cardiac death (SCD) persist. Nearly 1,000 deaths occur every day in the United States due to SCD. Data-based alternatives for SCD risk stratification dates back to the mid-1990s with the Cardiac Arrythmia Patient Outcomes Research Team (PORT) and several studies published in the American Heart Journal (September 2002, Volume 144). Although these were landmark studies, Mario Talajic, MD, Chief of Medicine, Montreal Heart Institute, Montreal, Canada, says “we still have limited clinical applications for what we’ve learned.”